Genetic architecture of host proteins involved in SARS-CoV-2 infection - Maik Pietzner (Nature Portfolio, 2020)
Finding effective treatments for COVID-19 depends upon understanding genetic regulation of proteins involved in SARS-CoV-2 infection and host response. Here, the authors identify genetic variants linked to expression of such proteins, data which could lead to the discovery of therapeutic targets.